"What countrey's this? and whither are we gone?" : papers presented at the twelfth International Conference on the Literature of Region and Nation, Aberdeen University, 30th July – 2nd August 2008 /: papers presented at the twelfth International Conference on the Literature of Region and Nation, Aberdeen University, 30th July – 2nd August 2008. (2010) - Unknown
No abstract available